Anti-Dumping and Anti-Trust Issues in Free-Trade Areas Revisited: A Comment on AfCFTA’s Protocol on Competition - Walker, Rebecca (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
Gabrielle Marceau devoted her Ph.D. thesis to the interaction between anti-dumping and anti-trust policies within free trade areas. The conclusions acknowledge that a robust and coordinated competition policy in both importing and exporting countries is crucial for avoiding the abuse of anti-dumping procedures and reaping the rewards of economic integration. Building on this premise, this article examines the use of competition policy for greater economic integration within regional trade agreements. To fully benefit from the integration process, the institutional framework and enforcement mechanisms of competition regimes must be tailored to specific policy objectives of the economic partnership. The design of the regional competition regulation and enforcement therefore matters. Taking a specific focus on the African Continental Free Trade Area’s Protocol on Competition (AfCFTA) this article offers a tailored approach to assessing its institutional design features and enforcement mechanisms. It draws lessons from those competition regimes embedded in other mega-regional RTAs and evaluates the Protocol on Competition’s general framework design in terms of AfCFTA’s policy objectives. The Protocol puts forward a multilayered approach to competition law enforcement with various national, regional, and supra-national actors addressing anti-competitive practices that fall within their respective jurisdictions. While this design responds to key challenges in establishing a continent-wide competition regime, the article concludes by identifying further focus areas for the regime’s implementation, with an eye to facilitating deeper economic integration.